Anti-cancer activity and mechanism of action of rice bran phytic acid on colon cancer in vitro and in vivo - Shafie, Nurul Husna (2013)
Colorectal cancer or colon cancer is a major neoplastic disease affecting men and women worldwide. Since Burkitt’s pioneering research that pointed to inverse relationship between colon cancer risk and consumption of fiber-rich foods, many epidemiological and laboratory animal studies have tested this hypothesis. The protective effects of dietary fiber on colon cancer development depend on the nature and source of fiber. Rice bran is one of the richest sources of dietary fiber and contains phytonutrients, including phytic acid, known to possess various medicinal properties. Phytic acid, or inositol hexaphosphate (IP6), is a polyphosphorylated carbohydrate, that has been suggested to play a significant role in the inhibition of colorectal cancer. Thus, our attention was drawn to the possibility to utilize the local source of phytic acid in identifying non-toxic anti-cancer agents that can potentially lead to the development of better treatments for colorectal cancer. In particular, the present study was aimed at investigating the anti-cancer effect of IP6 extracted from rice bran, in colon cancer model in vitro and in vivo. It began with the investigation of the inhibitory effect and associated mechanisms of rice bran IP6 on human colorectal cancer cell line, HT-29. IP6 induced marked growth inhibition in a dose and time dependent manner as evaluated by the MTT proliferation assay (IC50 = 12 μg/mL). Indeed, IP6 also did not cause any cytotoxicity towards normal 3T3 cells. Cell cycle progression studies were performed by flow cytometric analysis following propidium iodide (PI) staining of the cells. IP6 treatment (9.5, 12.0 and 14.5 μg/mL IP6) for 24, 48 and 72 hours, resulted in significant accumulation of G0/G1 phase cells (63 – 65 %) compared to control (50.53 %) (p<0.05). Together,these results suggested that IP6 causes the inhibition of cell growth through G0/G1 phase arrest in the cell cycle progression of HT-29 cells. Additionally, investigation of the ability of IP6 to induce colon tumor cell apoptosis was carried out. It was proven that IP6 significantly induced early apoptotic cell death (30 %) in a dose- and time dependent manner compared to control cells showing <1 % of cell death as confirmed by Annexin V assay (p<0.05). Quantitative real-time polymerase chain reaction (qRT-PCR) analysis was performed next followed by Western blotting to further determine apoptosis at the molecular level. Interestingly, IP6 showed an extensive significant reduction of anti-apoptotic Bcl-xl and a coherent increment of pro-apoptotic Bax at the mRNA and protein level. These results showed that IP6 caused a marked increase in apoptosis, which was accompanied by significantly increased mRNA and protein levels of caspase 3 and caspase 8 (p<0.05). These molecular alterations provide an insight into the apoptotic death of human colon cancer, HT-29 cells, elicited by IP6. The second part of this study in which the hypothesis whether IP6 extracted from rice bran had any effect on colon carcinogenesis was further investigated in an animal model of experimental colon cancer. Male Sprague-Dawley, weanling rats were divided into 5 groups with 12 rats in each group. Rats received two intraperitoneal (i.p.) injections of azoxymethane (AOM) in saline (15 mg/kg body weight) over a 2-week period for colon cancer induction. The IP6 treatments were given in three concentrations: 0.2 % (w/v), 0.5 % (w/v) and 1.0 % (w/v) via drinking water and the treatment were divided into two termination timelines. For the first termination, 6 rats from each group were killed after 8 weeks of IP6 treatment. The colons of these rats were analyzed for detection and quantification of aberrant crypt foci (ACF), an early biomarker of colon cancer. Analysis of ACF incidence demonstrated that administration of IP6 extracted from rice bran significantly reduced the total number of ACF (p<0.05). Furthermore, IP6 also significantly reduced the number of dysplastic and non-dysplastic ACF in a dose-dependent manner. For the second termination, the other 6 rats in each group were killed after 16 weeks of IP6 treatment. Colons of these rats were assessed for tumor incidence. It was shown that administration of phytic acid in the drinking water, significantly suppressed the total number of tumor incidences compared to the control (p<0.05). In another case, deregulation of the Wnt/β-catenin signaling pathway has been implicated in colorectal tumorigenesis resulting in accumulation of β-catenin, a major mechanism in the AOM-induced colon carcinogenesis model. Indeed, expression of enzymes associated with inflammation, such as inducible cyclooxygenase-2 (COX-2), has been shown to play a role in colon tumor progression. Therefore, the potential of IP6 in targeting key components of the Wnt/β-catenin signaling pathway and COX-2 as a rational for cancer drug discovery was demonstrated. Colon tumors were further analyzed for β-catenin and COX-2 expression at mRNA and protein level by qPCR and Western blot respectively. It was shown that administration of IP6 significantly down-regulated β-catenin and COX-2 expression in colon tumors as compared with control (no IP6 treatment) (p<0.05). Therefore, it can be suggested that β-catenin and COX-2 could be potential targets for colon cancer chemoprevention. Collectively, results presented in this study demonstrated that IP6 extracted from rice bran inhibited the proliferation of colon cancer in vitro selectively by arresting the cell cycle and thus leading to programmed cell death, which was later confirmed to be through the regulation of pro- and anti-apoptotic proteins and caspase dependent pathways. Moreover, the study in vivo with the AOM induced rat colon carcinogenesis model clearly showed that IP6 had inhibited the development of colon cancer through the suppression of ACF, leading to reduction in tumor incidence,which was via the down-regulation of β-catenin and COX-2 expression.